Bibliometric Analysis of ESG in Banking: What are the Key Directions and Collaborations Behind the Research? - Claudia GHERȚESCU; Alina Georgiana MANTA; Roxana Maria BĂDÎRCEA; Alia Gabriela DUȚĂ; Alexandra Lucia ZAHARIA (Finanţe: Provocările viitorului)
This study explores the trends and limitations of ESG research as applied to the banking sector, using a bibliometric analysis based on Scopus data. Using co-citation maps and collaborative networks between authors and institutions, the study highlights a fragmented literature with high thematic specialization and a low degree of interconnectedness between researchers, which limits the development of a coherent and integrated framework. The institutional analysis points to the existence of regional clusters, such as those in Spain, and an international group of prestigious but loosely interlinked institutions, indicating geographical isolation and a lack of comparative studies at a global level. Also, the differences in pace between recent and older research, accompanied by time lags, suggest a slow adaptation of some institutions to the new ESG paradigms, but also a continued evolution of academic collaborations. Despite these limitations, the maps highlight the importance of central institutions in updating research and integrating new ESG directions in banking. The study suggests the need for more extensive interdisciplinary and international research to overcome the barriers of specialization and isolation and to support a more comprehensive and integrated research framework.